2004
DOI: 10.1186/1471-2334-4-50
|View full text |Cite
|
Sign up to set email alerts
|

Zinc/copper imbalance reflects immune dysfunction in human leishmaniasis: an ex vivo and in vitro study

Abstract: Background: The process of elimination of intracellular pathogens, such as Leishmania, requires a Th1 type immune response, whereas a dominant Th2 response leads to exacerbated disease. Experimental human zinc deficiency decreases Th1 but not Th2 immune response. We investigated if zinc and copper levels differ in different clinical forms of leishmaniasis, and if these trace metals might be involved in the immune response towards the parasite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 21 publications
(26 reference statements)
6
41
0
Order By: Relevance
“…One of these is acute cutaneous leishmaniasis, induced by different forms of Leishmania. Patients with cutaneous, mucosal, and visceral leishmaniasis display lower plasma zinc levels [161]. As a result of zinc therapy, a dose--dependent decrease in erythemas and size of induration and an increased cure rate were found [147].…”
Section: Parasitic Infectionsmentioning
confidence: 99%
“…One of these is acute cutaneous leishmaniasis, induced by different forms of Leishmania. Patients with cutaneous, mucosal, and visceral leishmaniasis display lower plasma zinc levels [161]. As a result of zinc therapy, a dose--dependent decrease in erythemas and size of induration and an increased cure rate were found [147].…”
Section: Parasitic Infectionsmentioning
confidence: 99%
“…Van Heugten et al (2003) reported that pigs supplemented with Zn had greater lymphocyte proliferation than pigs fed the control diet. Meanwhile, Weyenbergh et al (2004) reported that increased Cu levels inhibited in vitro IFN-γ production. Pocino et al (1991) showed decreased lymphocyte proliferation in response to concanavalin A in mice fed excess Cu, but it was increased in response to E. coli lipopolysaccharide stimulation, whereas Davis et al (2002) indicated no response of lymphocytes of pigs fed pharmacological levels of dietary Cu.…”
Section: Immune Responsementioning
confidence: 99%
“…Deficiencies of Zn and Cu reduce immune function and increase susceptibility to disease (Neldner and Hambidge 1975;James 1990;Stabel and Spears 1990). Bao et al (2003) reported that Zn supplementation might reduce the gene expression for cytotoxic cytokines that increase amounts of free radicals, whereas Weyenbergh et al (2004) increased Cu levels inhibited in vitro interferon-γ (IFN-γ) production. Although the immune function is well established, the impact of feeding pharmacological levels of dietary Zn and Cu in the short and medium terms are not well established in young piglets.…”
mentioning
confidence: 99%
“…On the other hand, zinc is an essential trace element for humans and its deficiency leads to decreased recruitment of naive T cells and reduced expression of Th1 cytokines (IFN-␥, interleukin-2, and tumor necrosis factor alpha) (26). This immune impairment could explain in part observations made in patients with mucocutaneous and visceral leishmaniasis in whom significantly lower plasma levels of zinc were found compared to normal endemic controls (27). Therefore, supplementing zinc in a deficient host could favor the development of a protective Th1-mediated response against Leishmania.…”
mentioning
confidence: 80%